THU0602 THE ROLE OF INFRARED THERMOGRAPHY IN THE ASSESSMENT OF PERIPHERAL VASCULOPATHY AND IN THE THERAPEUTIC MANAGEMENT OF SYSTEMIC SCLEROSIS PATIENTS TREATED WITH SYNTHETIC PROSTANOIDS. (June 2019) - Cecchi, Irene; Radin, Massimo; Rubini, Elena; Foddai, Silvia Grazietta; Rossi, Daniela; Sciascia, Savino; Roccatello, Dario
Abstract : Background: Skin lesions represent the leading feature of systemic sclerosis (SSc), with Raynaud's phenomenon (RP) the most frequent and early clinical manifestation of the disease. Digital vasculopathy severely affects SSc patients, lowering their quality of life and negatively impacting on their daily functions. Digital ulcers is associated with poor cardiovascular prognosis and decreased survival rate [1]. Nevertheless, standardized treatment strategies and non-invasive tools for the management of RP and SSc skin manifestations are badly needed. Objectives: The aim of this study was a) to evaluate the efficacy of infrared thermography in the assessment of peripheral vasculopathy in a cohort of SSc patients treated with cyclic intravenous infusions with synthetic prostanoids b) to identify those patients who might benefit from an intensified infusional treatment protocol with prostanoids. Methods: Twenty-six SSc patients [2], attending our Department for their routinely 28-days apart intravenous therapy with prostanoids (Iloprost) based on the presence of severe secondary RP and/or digital ulcers, were enrolled in this study. Thermographic evaluation of both hands was made at baseline (T0), and at days 14 and 28 after the first prostanoid infusion (named T1 and T2, respectively). Statistical analyses have been performed and a p-value <0.05 was considered statistically significant. Results: A total of 26 SSc patients, 24 (92.3%) female, mean age 65.3±12.6 yrs, mean disease duration at time of data collection 12.4±6.6 years, were prospectively enrolled in the study. Among them, 15 patients (57.7%) presented with limited cutaneous SSc, while 11 patients (42.3%) showed an extra-cutaneous form of the disease. Demographic, clinical, and laboratory characteristics of the patients included in the study are detailed in Table 1 . The thermographic assessment showed a substantial stability of the temperature values when comparing T0 and T1 (mean differences of the right hands 0.4 ±5.6; mean differences of the left hands 1.2 ±4.5), while they are significantly reduced when comparing T1 and T2 (mean differences of the right hands -3.1 ± 9.3, p=0.049; mean differences of the left hands -3.4 ±8.5, p=0.012 respectively) (Figure 1A ). When stratifying according to clinical manifestation, a higher differences in temperature variations were observed between T1 and T2 in SSc patients with systemic involvement, when compared to those with limited cutaneous SSc (mean of the differences of the right hands -5.0 ±11; mean of left-hands differences -4.9 ±11.5 Vs. mean right-hands differences -2.5 ±11; mean left-hands differences -3±8.6; p=0..035 respectively) (Figure 1B ). Conclusion: Thermography could represent a reliable, non-invasive, manageable and cost-effective method for the assessment and monitoring of peripheral vasculopathy in patients with SSc. These data also show that SSc patients with systemic involvement could benefit more from an intensified infusion protocol with prostanoids compared to SSc patients with a limited skin form of the disease. Thermography has shown excellent potential to be a reliable and objective outcome measures to facilitate clinical trials of novel treatments SSc-related RP. References: [1] Mihai C, et al. Digital ulcers predict a worse disease course in patients with systemic sclerosis. Ann Rheum Dis2016;75:681–6. [2] van den Hoogen F, et al. 2013classification criteria for systemic sclerosis: an ACR/EULAR collaborative initiative.Arthritis Rheum. 2013 Nov;65(11):2737-47. Disclosure of Interests: None declared